English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I just need the process, not the answer. I want to solve most of it, I just am having trouble and I dont know what i am doing wrong.

2006-09-17 17:09:46 · 22 answers · asked by Anonymous in Science & Mathematics Mathematics

22 answers

the answer is - 9

-3*3x+(-3)*15-10-x=35

-9x-45-10-x=35
-9x-x-45-10=35
-10x-55=35
-55-35=10x

10x=-90

x=-90/10=-9

2006-09-17 17:13:41 · answer #1 · answered by iyiogrenci 6 · 0 0

First multiply the -3 with the numbers in the ()

-3(3x+15) - (10+x) = 35

-9x+(-45) - (10+x) = 35

then u must remember that anything outside the () you have to multiply it by that so,

-(10 + x) will be -10 - x

then group the numbers in the equation,

-9x - x - 45 - 10 = 35

-10x - 55 = 35

then isolate the x

-10x = 35 + 55

-10x = 90

then divide each side by -10

-10x/-10 = 90/-10

x = -9

then check you answer by entering -9 into the original equation

-3(3(-9) + 15) - (10 + (-9) =

-3(-27 + 15) - (1) =

-3(-12) - 1 = (remember two negatives multiplied equals a positive)

36 - 1 = 35

2006-09-18 00:25:21 · answer #2 · answered by KryBaby 4 · 0 0

-3(3x+15) - (10+x) = 35

now multiplying the first bracket by -3 and the second bracket with -1 (cuz - outside a bracket is as good as multiplying the bracket with -1)

-9x - 45 - 10 - x = 35

Now for the sake of simplicity keep the X's on one side and the numbers on the other

-9x - x = 35 + 10 + 45 (since 45 and 10 were taken to the other side the signs change)

-10x = 45 + 45

-10x = 90

divide both sides by 10

-x = 9

now divide both side by -1
hence

x = -9

2006-09-20 13:39:09 · answer #3 · answered by rav142857 4 · 0 0

first you apply the distributive property. So you multiply what's outside the parenthesis with what's inside. with the minus in between you just imagine it's -3(3x+15)+(-1)(10+x)
So: -9x-45-10-x=35
I multiplied the -3 with the 3x and the 15 separately. did the same with the -1.
now you add: -10x-55=35
you pass the -55 to the other side: -10x=35+55
and voliá: x=90/-10
x=-9

be careful, many of the answers are terribly wrong.
hope you get it!

2006-09-18 00:17:15 · answer #4 · answered by Anonymous · 0 0

Step I
Collect the terms in x in the lhs of the equation, disregarding the other expressions. So the expression in the lhs now is equal to:
(-9x - x) = -10x

Step 2
Transfer all the terms not in x to the rhs. The existing term 35 in the rhs would be unaltered, but the transferred terms from lhs will change in sign. So + 5 say in rhs would become -15, while -5 in -1 in rhs would become 1.
So, expression in the rhs = 35+ 45+ 10 = 90

Step 3

lhs = rhs; and so,
- 10x = 90
gining, x = -9.

NOTE:
Coming back to your original question, you can check whether you have properly changed the sign during the transfer.

2006-09-19 14:39:22 · answer #5 · answered by K Sengupta 4 · 0 0

Using distributive property you multiply the #'s outside the parenthesis with the inside ones giving you:
-9x-45-35=10+1x
Then you put the numbers containing x on one side of the =sign and the plain #'s on the other: (if you move a number to the opposite side of the =sign, it's sign changes, but if it's on the same side as before it's the same sign as before)
-9x-80=10+x
Now consolidate:
-10x=90
divide both sides by -10 to solve for x
x= -9

THE -9 ANSWERS ARE RIGHT!!!!!!!!!!! All others are wrong

2006-09-18 00:17:35 · answer #6 · answered by Anonymous · 0 0

You would X the first number in the barackets so -3x 3X+3x15 =
-9x-45. When you multiply a positive by a negative it becomes a negative, then you would subtract that from 10+X=35. But you would have to get all the X's on one side and the original numbers on the other to get the value X. So...
Yeah you can go from there cuz I kept tryin to figure it out and I coudlnt figure out the correct answer either soo math.com for u )

2006-09-18 00:28:50 · answer #7 · answered by TOokieTook 3 · 0 0

distributive property:

-3(3x) + (-3)(15) -10 -x = 35
-9x + -45 -10 -x= 35
-10x -55=35
-10x = 90
x = 90/-10
x=-9

2006-09-18 01:23:53 · answer #8 · answered by sharon t 2 · 0 0

-3(3x + 15) - (10 + x) = 35

Multiply out the first and second term

-9x -45 - 10 - x = 35

Combine like terms

-10x - 55 = 35

Add 55 to both sides

-10x = 90

Divide both sides by -10

x = -9

2006-09-18 00:20:19 · answer #9 · answered by jhy 2 · 0 0

-3(3x+15)-(10+x)=35
first concentrate on the numbers in parentheses, if you cant do anything with that, concentrate on what is directly outside the parentheses, which in this case its -3, so you times that number to everything in the parentheses, if there is no number outside the parentheses, then they are multiplied by one, in this case (10 + x) is multiplied by negative one since it has a minus sign. After you get everything out of the parentheses, get all the regular numbers over to the other side of the equal sign, and all the letters together. in order to get all the regular numbers you do the opposite to them, in this case, after you get all the numbers out of the parentheses, you will have a -45 and a -10, add them to the other side, so you will have 35 + 45 + 10 after that, just keep breaking it down until you have your answer.

2006-09-18 00:26:35 · answer #10 · answered by Anonymous · 0 0

first multiplie the -3 in the first group
so you get (-9x+5)-(10+x) now multipy the second group by negative
so you get -9x+5-10-x =35
now add up the X's .. -9x-x+5-10 = 35
then -10x-5 = 35
divide by 5 for all of them
-2x-1=7
move the one to the other side (this operation changes the sign of it)
so you'll have -2x = 7+1
-2x = 8
then divide by -2 to get what x equals to :
x = 8/-2
x = -4 and that's the answer !
good luck

2006-09-18 00:15:17 · answer #11 · answered by JoToCo 3 · 0 1

fedest.com, questions and answers